Profile of Trichoepithelioma Patients at Hospital for the Period of 2016-2021 - Fauziah Hannum; Ennesta Asri; Muhammad Zulfadli Syahrul (GLOBAL HEALTH SCIENCE GROUP, 2024)
Trichoepithelioma is a rare benign tumor of the skin adnexa, of the pilosebaceous unit, especially of the hair follicle. This tumor is characterized by the appearance of lesions in the form of papules or nodules that are the color of the skin, with a size of 2-8 mm which can have solitary or multiple distribution. Trichoepithelioma has a psychosocial impact for sufferers, because trichoepithelioma lesions are often found on the face so that many sufferers feel embarrassed. This study is a retrospective descriptive study with a cross-sectional design that aims to determine the profile of trichoepithelioma based on age, gender, clinical picture, predilection site, duration before therapy, histopathological examination, treatment modality, and recurrence after therapy. From the 15 samples studied, it was found that the age group 11-19 years was the age group with the most trichoepithelioma patients (66.7%) with the highest gender being female (66.7%). All patients had clinical features of multiple trichoepithelioma (100%) with the greatest predilection for the nose (34.1%). Most of the patients had the same family history as the patient (66.7%). The duration of most patients 6 years (53.3%). Most of the patients did not perform histopathological examination (53.3%). The modality of therapy given to all patients was electrocautery with curettage (100%). Most of the patients did not follow up again regarding their recurrence (60%). Meanwhile, the most patients who did follow-up related to recurrence were <1 year (33.3%).